High-speed rail in the UK delegate information : Monday 8 May 2006, venue, Royal Institute of British Architects, London, UK. (Thomas Telford, 2006)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held at RIBA held on 8 May 2006.